Representasi Realitas Sosial dalam Novel Seporsi Mie Ayam Sebelum Mati Karya Brian Khrisna: Kajian Sosiologi Sastra Alan Swingewood: Penelitian - Kadir, Herson; Achmad Bagtayan, Zilfa; Mangilo, Nurhalima; S. Daud, Yuniarti; Mongilong, Melani (Lembaga Penelitian dan Pengabdian Masyarakat, 2025)
This study aims to reveal the representation of social reality in Brian Khrisna's novel Seporsi Mie Ayam Sebelum Mati (Chicken Noodles Before Dying) using Alan Swingewood's sociological approach to literature. Through qualitative descriptive analysis, this study examines how the social conditions of modern society are reflected through experiences in the novel. The results of the analysis show that this novel presents three main forms of social reality, namely poverty, social injustice, and crime. Poverty is depicted through people's lives full of economic limitations and life pressures that make them trapped in a cycle of decisions. Injustice in families often arises when rules are not applied consistently. Meanwhile, crime arises as a consequence of deep-rooted economic and social pressures, showing how violence and criminal acts are part of the dynamics of harsh urban society. Based on Swingewood's theory, this novel functions as a reflection of social reality as well as a critique of inhumane social conditions. Thus, Seporsi Mie Ayam Sebelum Mati not only presents the personal stories of its characters, but also presents a portrait of complex social life in contemporary society.